WACANA SUBORDINASI PEREMPUAN DALAM KOMERSIALISASI “RUANG PUBLIK” (Analisis Wacana Kritis Sara Mills Pada Rubrik ‘DetEksi’ Jawa Pos) - Adi Kurnia Djarot Nahusona; Sih Natalia Sukmi (Cakrawala Jurnal Penelitian Sosial, 2014)
"Public Sphere", which now form the mass media, contributing significantly to the struggle of women. Aspirations of women who had been confined in the domestic realm, became more a place, after public sphere began to appear. At the time of the Republic of Indonesia into the world spotlight, because the lower level of the reader for the young, DetEksi rubric come up and amplifying the voices of youth. The emergence rubric DetEksi be interesting, seeing that the theme is being discussed, always involves respondents in large quantities, which consists of women and men, which can be freely as if expressing their aspirations. This study aimed to describe the discourse of subordination of women in the public sphere. Critical discourse analysis used in this study, as in the view of Sara Mills, the media has been very biased in presenting women. The method used in this study is a qualitative approach, with a descriptive study. Results of research conducted by the researchers revealed that, of the 11 analyzes conducted, all laden with patriarchal culture, women are subordinatedKeywords: Public Sphere, Mass Media, Aspirations of Women.